Differences in depression,anxiety and stress between low and high-achieving students - Md. Yasin, Md. Aris Safree; Dzulkifli, Mariam Adawiah (Universiti Malaysia Terengganu Publisher, 2011)
This study was conducted to examine the differences in depression, anxiety, and stress between low-and high-achieving students. 120 undergraduate students of the International Islamic University Malaysia (IIUM) were involved in this study. The Depression Anxiety Stress Scale (DASS) was used to measure the depression, anxiety, and stress among students. Independent Sample T-test was used to differentiate the depression, anxiety, and stress between low-and high-achieving students. The findings of this study revealed that there were significant differences in depression, anxiety, and stress between low-and high-achieving students. The findings of the study will be useful in assisting educators, counsellors, psychologists, and researchers to develop strategies to enhance students’ psychological well-being.